Two new species of the ladybird beetle Hong Ślipiński from Chile (Coleoptera: Coccinellidae: Microweiseinae) - González, Guillermo; Escalona, Hermes E. (Zootaxa, 2013)
The ladybird beetle genus Hong Ślipiński was previously known from a single female specimen from a subtropical forest in South East Queensland, Australia. Hong guerreroi sp. nov. and H. slipinskii sp. nov. from a temperate forests of Central and Southern Chile are described and illustrated. A key for the species of the genus and complementary characters, in-cluding the first description of males, are provided.